Variety of future-orientation: The case of G-19 countries - Horst Hanusch; Yasushi Hara (Universität Augsburg, Institut für Volkswirtschaftslehre, 2016)
In modern growth or development theory innovation is a crucial factor which pushes the dynamics of an economy and determines its success in the future. Out of innovations, created in the presence, the potentials for the future of a country are prepared, deciding how its economic fitness and competitiveness will emerge. So, future-orientation is in a natural way connected with innovativeness of a firm, a region or a country and shapes the strength and the specifics of the process of development. Our study is focusing on the group of G-19 countries with respect to their future-orientation shaped and characterized by innovation and the underlying processes of creating and distributing novelties. This group is an economic, financial and political forum which consists of 19 major economies, advanced and developing ones, allocated in Asia, Europe, Euro-Asia, North and South America, The Middle East and Oceania. If you add the European Union you get the G-20 group which is the main economic council of wealthy nations nowadays. The concept of future-orientation, defined by innovativeness, gets its analytical and empirical relevance when it is placed and investigated within a specific development model. Such a model determines the theoretical basis of the study and provides the necessary ingredients for an empirical application. In our study we will use "Comprehensive Neo-Schumpeterian Economics" (CNSE) as an analytical framework (Hanusch and Pyka, 2007a). This approach is based (a) on the principle of innovation as the main driving force and the engine of development coupled b) with the notion of future-orientation penetrating all spheres of socio-economic life in developed as well as in developing countries. Based on the concept of CNSE the central aim of our study is to gain new insights and findings concerning the variety of future-orientation of the G-19 countries. For that purpose we use an empirical indicator approach which (a) tries to bring the notion of future-orientation on a concrete basis by using indicators embedded in the framework of CNSE; (b) investigates patterns of similarities in the set of indicators; (c) shows how these patterns look like by applying cluster analysis; (d) draws some conclusions from the patterns concerning the status and variety of future-orientation in the group of G-19 countries.
urn:nbn:de:bvb:384-opus4-710715
Keywords: B52; C8; O57; 330; Development Models; Neo-Schumpeterian Economics; Indicator Analysis; Cluster Analysis